Menstrual Hygiene Awareness, Practices and Health Implications Among Adolescent Girls in Ukpom Abak, Akwa Ibom State, South-South Nigeria - Ekpin VI; Johnson OE; Ukpong DE; Akpan EB; Obimah S; Udo ME; Bassey CD; Uyoho PE; Inemesit AE (Ibom Medical Journal)
Background: Menstrual hygiene management (MHM) is crucial for the health and well-being of adolescent girls. In many developing countries, including Nigeria, awareness and resources for proper MHM are lacking. This study aimed to assess the awareness, practices and associated menstrual hygiene health problems related to among adolescent girls in Ukpom Abak.